2019
DOI: 10.1080/15412555.2019.1634039
|View full text |Cite
|
Sign up to set email alerts
|

Adherence to a Mediterranean-like Diet as a Protective Factor Against COPD: A Nested Case-Control Study

Abstract: A diet rich in nutrients has been suggested to have protective effects against the development of chronic obstructive pulmonary disease (COPD). Since the traditional Mediterranean diet is high in nutrients, including antioxidants, vitamins, and minerals, it is of interest to study as a protective factor against COPD. Our aim was therefore to study its associations with development of COPD using population-based prospective data from the V€ asterbotten Intervention Programme (VIP) cohort. Data on diet from 370 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 39 publications
1
24
0
Order By: Relevance
“…Based on the overall quality rating of these 10 studies, four were determined to be "good", five "fair" and one "poor". The other two included studies were case-control studies by ARDESTANI et al [22] and FISCHER et al [36], which were evaluated using a different NIH-QAT checklist and were thus not included in the table. The study by ARDESTANI et al [22] was deemed to be of overall "fair" quality, with several concerns: it was unclear if all eligible cases and/or controls were invited to participate, it was unclear whether dietary exposure occurred prior to the development of COPD and there was uncertain blinding status of assessors.…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on the overall quality rating of these 10 studies, four were determined to be "good", five "fair" and one "poor". The other two included studies were case-control studies by ARDESTANI et al [22] and FISCHER et al [36], which were evaluated using a different NIH-QAT checklist and were thus not included in the table. The study by ARDESTANI et al [22] was deemed to be of overall "fair" quality, with several concerns: it was unclear if all eligible cases and/or controls were invited to participate, it was unclear whether dietary exposure occurred prior to the development of COPD and there was uncertain blinding status of assessors.…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%
“…The study by ARDESTANI et al [22] was deemed to be of overall "fair" quality, with several concerns: it was unclear if all eligible cases and/or controls were invited to participate, it was unclear whether dietary exposure occurred prior to the development of COPD and there was uncertain blinding status of assessors. The study by FISCHER et al [36] was deemed to be of overall "fair" quality, with several concerns, including that there was no sample size justification, there was no clear use of concurrent controls and it was unclear whether dietary exposure occurred prior to COPD development. Healthy dietary patterns and COPD The pooled effect estimates of five cross-sectional analyses (figure 2) (OR 0.88, 95% CI 0.82-0.94) and three cohort studies (figure 3) (RR 0.56, 95% CI 0.37-0.84) suggested a lower risk of COPD in those adhering to a healthy dietary pattern.…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%
“…This pathology is strongly influenced by genetics, environmental and behavioral factors, including physical inactivity and diet. In the last twenty years, several studies have shown that the MeD, particularly rich in fruit, nuts, vegetables, fish and whole grains, is associated with a reduced risk of COPD [ 122 , 123 , 124 , 125 ]. This observation suggests that the amount of antioxidant compounds provided by the aforementioned components can reduce the occurrence of an oxidative microenvironment in the lung.…”
Section: The Mediterranean-type Dietary Patternmentioning
confidence: 99%
“…This observation suggests that the amount of antioxidant compounds provided by the aforementioned components can reduce the occurrence of an oxidative microenvironment in the lung. Moreover, the anti-inflammatory properties of omega-3 fatty acids, as well as the pro-inflammatory properties of omega-6 fatty acids, might be crucial, considering the pivotal role played by inflammation in COPD progression [ 125 ]. Finally, the lower amount of processed meat might contribute to the reduction in an oxidative stress condition in the lung: of note, a recent meta-analysis demonstrated that each 50 g of the increased intake of processed meat per week was associated with an 8% increased risk of developing COPD [ 126 ].…”
Section: The Mediterranean-type Dietary Patternmentioning
confidence: 99%
“…Studies have shown that microorganisms play a protective role in allergic disorders [97,98]. Finally, the fact that MD is characterized by richness of beneficial nutrients, may be the main reason for the inverse association with chronic obstructive pulmonary disease (COPD) according to A.Fischer et al [99].…”
Section: Allergic Diseases and Asthmamentioning
confidence: 99%